Separation of CO2 from Small Gas Molecules Using Deca-Dodecasil 3 Rhombohedral (DDR3) Membrane Synthesized via Ultrasonically Assisted Hydrothermal Growth Method - Muhammad Mubashir; Yeong Yin Fong; Sidra Saqib; Ahmad Mukhtar; Sikander Rafiq; Muhammad Bilal K. Niazi; Muhammad Babar; Sami Ullah; Abdullah G. Al-Sehemi; Farrukh Jamil (Advances in Polymer Technology)
Deca-dodecasil 3 rhombohedral (DDR3) membrane has received much attention in CO2 separation from small gas molecules because of its molecular sieving property and stable characteristics. Therefore, the present work is focusing on the utilization of previously fabricated membrane (synthesized in 3 days as reported in our previous work) to study the effect of hydrocarbons and its durability at the previously optimized conditions. Subsequently, gas permeation study was conducted on the DDR3 membrane in CO2 separation from small gas molecules and it was found that the permeance of H2, CO2, N2, and CH4 decreased in the order of H2 > CO2 > N2 > CH4, according to the increase in kinetic diameter of these gas molecules. Besides, it was observed that the ideal selectivities of the gas pairs decreased in the sequence of CO2/CH4 > CO2/N2 > H2/CO2. On the other hand, it was found that the presence of hydrocarbon impurities in the gas mixture containing CO2 and CH4 has directly affected the performance of DDR3 membrane and contributed to the losses of CO2 permeability, CH4 permeability, and CO2/CH4 selectivity of 39.1%, 14.8%, and 4.2%, respectively. Consequently, from the stability test, the performance of DDR3 membrane remained stable for 96 h, even after the separation testing using CO2 and CH4 gas mixture containing hydrocarbon impurities.